2021
DOI: 10.1016/j.bbih.2021.100254
|View full text |Cite
|
Sign up to set email alerts
|

Innate immunity impacts social-cognitive functioning in people with multiple sclerosis and healthy individuals: Implications for IL-1ra and urinary immune markers

Abstract: Social-cognitive difficulties can negatively impact interpersonal communication, shared social experience, and meaningful relationships. This pilot investigation examined the relationship between social-cognitive functioning and inflammatory markers in people with multiple sclerosis (MS) and demographically-matched healthy individuals. Additionally, we compared the immune marker profile in serum and urine-matched samples. Social cognitive functioning was objectively assessed using The Awareness of Social Infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…These factors have previously been implicated in cognitive function. For example, in adults with multiple sclerosis, a higher serum concentration of the anti-inflammatory marker IL-1RA was associated with better social-cognitive functioning ( 43 ). A study of 42 adults with bipolar disorder found that IL-7 levels were significantly associated with measures of cognition, showing higher levels in the cognitively unimpaired group and a positive correlation with cognitive performance ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…These factors have previously been implicated in cognitive function. For example, in adults with multiple sclerosis, a higher serum concentration of the anti-inflammatory marker IL-1RA was associated with better social-cognitive functioning ( 43 ). A study of 42 adults with bipolar disorder found that IL-7 levels were significantly associated with measures of cognition, showing higher levels in the cognitively unimpaired group and a positive correlation with cognitive performance ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The urinary neopterin appeared as a potential marker that could differentiate multiple sclerosis from other demyelinating patient groups such as myelin oligodendrocyte glycoprotein antibody-associated disorder and neuromyelitis optica spectrum disorders [ 40 ]. And urine interferon-gamma-inducible protein-10, and macrophage inflammatory protein-1 β were associated with poorer social–cognitive abilities in multiple sclerosis patients [ 41 ]. Also, urinary toll-like receptor 2-stimulant levels are significantly elevated in multiple sclerosis patients [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, TF analysis revealed alteration of several additional components of the Myc/Max/Mad network in female mice in addition to the common components altered in both sexes, possibly suggesting that nicotine-induced deacetylation of the Myc/Max/Mad network is stronger in female mice. Innate immune responses can lead to synaptic and circuit dysfunction, which have been shown to increase vulnerability to cognitive decline and neurodegeneration in humans (Cribbs et al, 2012; Haroon et al, 2017; Turner et al, 2021). Thus, it is possible that nicotine inhibits VD performance via activation of innate immune responses in female mice.…”
Section: Discussionmentioning
confidence: 99%